Answer:
✨what are the statements.? you didnt label them ✨
Step-by-step explanation:
✨GOD LOVES YOU✨
And welcome to brainly!
Answer:
the answer and explanation of the question is in the picture
Step-by-step explanation:
hope this helps
please like and Mark as brainliest
Answer:
(3, 3 )
Step-by-step explanation:
Given the 2 equations
3x - y = 6 → (1)
6x + y = 21 → (2)
Adding the 2 equations term by term will eliminate y, that is
(6x + 3x) + (y - y) = (21 + 6), that is
9x = 27 (divide both sides by 9 )
x = 3
Substitute x = 3 into either (1) or (2) and solve for y
Using (2), then
(6 × 3) + y = 21
18 + y = 21 ( subtract 18 from both sides )
y = 3
Solution is (3, 3 )
Answer:
what do u need help with lol
Step-by-step explanation:
Answer: a = 23 ft.
Reasoning:
The question asks for the value of the leg a, given the tangent of the opposite angle and the length of the adjacent-leg, b.
The ratio that relates the three parameters is:
tan(A) = opposite-leg / adjacent-leg = a / b = a / 23 ft
Solve for a, wich is the unknown:
a = 23ft * tan(A) = 23ft * 1.0 = 23 ft
Answer: 23 ft.